Selling sex in the Reich prostitutes in German society, 1914-1945 - Harris, Victoria (Victoria Thomasin) (Oxford University Press, 2010)
Harris focuses on the experiences of prostitutes working in the German sex trade in the first half of the 20th century. She develops a nuanced picture of the prostitutes' backgrounds their reasons for entering the trade and their attitudes towards their work and those who sought to control them.